1986
DOI: 10.1056/nejm198606193142502
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adjuvant Chemotherapy on Relapse-Free Survival in Patients with Osteosarcoma of the Extremity

Abstract: We conducted a randomized controlled trial to determine whether intensive multi-agent adjuvant chemotherapy improves the chances of relapse-free survival in patients with nonmetastatic high-grade osteosarcoma of the extremity, as compared with concurrent controls. After undergoing definitive surgery, 36 patients were randomly assigned to adjuvant chemotherapy or to observation without adjuvant treatment. At two years the actuarial relapse-free survival was 17 percent in the control group, similar to that found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
550
4
22

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,075 publications
(585 citation statements)
references
References 20 publications
9
550
4
22
Order By: Relevance
“…The long‐term survival of osteosarcoma patients has improved dramatically because of the introduction of effective systemic chemotherapy 1, 2, 3, 4. Recent studies have demonstrated a more favorable outcome, especially for patients with nonmetastatic osteosarcoma 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…The long‐term survival of osteosarcoma patients has improved dramatically because of the introduction of effective systemic chemotherapy 1, 2, 3, 4. Recent studies have demonstrated a more favorable outcome, especially for patients with nonmetastatic osteosarcoma 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary survival rates in patients with localized disease have been reported in the range of 65-75% for Ewing's sarcoma [4][5][6][7] and 65-90% for osteosarcoma [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Adjuvant and postoperative chemotherapy can reduce micrometastases and tumor size. 6,8,9 Nevertheless, 40% of all osteosarcoma patients experience relapse within 5 years, and relapse carries a 70% 5-year mortality rate. 9,10 Nearly 30% of relapsing patients develop lung metastasis within the first year, and the 2-year survival rate for metastatic osteosarcoma is Յ30%.…”
mentioning
confidence: 99%
“…6,8,9 Nevertheless, 40% of all osteosarcoma patients experience relapse within 5 years, and relapse carries a 70% 5-year mortality rate. 9,10 Nearly 30% of relapsing patients develop lung metastasis within the first year, and the 2-year survival rate for metastatic osteosarcoma is Յ30%. 9,11 The obstinate clinical course of osteosarcoma despite aggressive standard therapy demands the investigation of new treatment approaches.…”
mentioning
confidence: 99%
See 1 more Smart Citation